2010
DOI: 10.32607/20758251-2010-2-3-62-71
|View full text |Cite
|
Sign up to set email alerts
|

PEDF - A Noninhibitory Serpin with Neurotrophic Activity

Abstract: The pigment epithelium-derived factor (PEDF) is a glycoprotein with a molecular weight of 50 kDa belonging to the noninhibitory serpin family. It regulates several physiological processes, such as stimulation of retinoblastoma cell differentiation into neuron cells, and facilitation of the growth and viability of photoreceptor cells and neurons of the central nervous system. Moreover, this factor protects neuronal cells against apoptosis. PEDF is not only a neurotrophic factor, but also a natural angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…It was first discovered in the culture medium of human fetal retinal pigment epithelial cells as a neurotrophic factor 22 . Recent studies have shown that PEDF is widely expressed throughout fetal and adult tissues and has multiple important functions, including differentiation, neuroprotective effects, and antiangiogenic effects on different cells or tissues 23 . Our previous study demonstrated that the insufficient secretion of PEDF within the cavernous tissue was involved in CNIED 24 .…”
Section: Introductionmentioning
confidence: 99%
“…It was first discovered in the culture medium of human fetal retinal pigment epithelial cells as a neurotrophic factor 22 . Recent studies have shown that PEDF is widely expressed throughout fetal and adult tissues and has multiple important functions, including differentiation, neuroprotective effects, and antiangiogenic effects on different cells or tissues 23 . Our previous study demonstrated that the insufficient secretion of PEDF within the cavernous tissue was involved in CNIED 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Although PEDF promotes the apoptosis of endothelial cells, it exerts a synergistic proliferative effect on endothelial cells with VEGF [ 24 ]. Current studies shows that PEDF is widely expressed throughout fetal and adult tissues and has multiple important functions including differentiation, neuroprotection, and antiangiogenic effects on different cells or tissues [ 25 ]. Recently, Vigneswara et al demonstrated that PEDF has neuroprotective and axogenic effects on retinal ganglion cells in an optic nerve crush injury model [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present Letter is devoted to the discussion of possible a solution of DE-and DM-problems in the frame of the Poincaré gauge theory of gravity (PGTG) (see [8,9,10,11]), which is a natural generalization of GR and which offers opportunities that can solve the principal problems of Einstein gravitational theory (see [12,13] and references herein). The PGTG is based on well-known and acceptable physical principles including the local gauge invariance principle, and it is the gravitation theory in 4-dimensional physical spacetime with the structure of the Riemann-Cartan continuum.…”
Section: Introductionmentioning
confidence: 99%
“…By using sufficiently general expression of L g regular isotropic cosmology including inflationary cosmology was built and investigated in the frame of PGTG (see [17,18,19,20] and references herein). As it was shown, the character of gravitational interaction by certain physical conditions in the frame of PGTG is changed, and in the case of usual gravitating matter with positive values of energy density and pressure the gravitational interaction can be repulsive [13,17,19] that offers opportunities to solve principal problems of GR, in particular, the problem of the beginning of the Universe in time in the past (problem of cosmological singularity). The possible solution of DE-problem in the frame of PGTG was discussed in [20].…”
Section: Introductionmentioning
confidence: 99%